Synthesis Octyl p-Methoxycinnamate as Sunblock by Transesterification Reaction with the Starting Material Ethyl p-methoxycinnamate - Suzana, .; Irawati, Nunuk; Budiati, Tutuk (Indonesian Journal of Cancer Chemoprevention, 2011)
SynthesisÃÂ  octylÃÂ  p-methoxycinnamateÃÂ  substanceÃÂ  asÃÂ  sunblock,ÃÂ  hasÃÂ  beenÃÂ  doneÃÂ  by transesterificationÃÂ  reaction.ÃÂ  TheÃÂ  startingÃÂ  materialÃÂ  ofÃÂ  theÃÂ  reactionÃÂ  wasÃÂ  ethylÃÂ  p-methoxycinnamateÃÂ  isolatedÃÂ  fromÃÂ  KaempferiaÃÂ  galangaÃÂ  L.TheÃÂ  transesterificationÃÂ  reactionÃÂ  was carried out by reactingÃÂ  ethyl p-methoxycinnamate with octanol. The product was identified by UV-VIS,Infra Red and Mass Spectroscopy. The result of measurements on erythemic %T at various concentrations demonstrate that octyl p-methoxycinnamate is applicable as a sunblock compound. KeyÃÂ  wordsÃÂ  :ÃÂ  octylÃÂ  p-methoxycinnamate,ÃÂ  transesterification,ÃÂ  ethylÃÂ  p-methoxycinnamate,ÃÂ  sunblock